2 Peter reconsidered - Green, E. Michael B.; Tyndale Fellowship for Biblical Research (London, UK Tyndale, 1961)
Includes bibliographical references.
Lecture delivered in Cambridge on July 8th, 1960 for a meeting convened by the Tyndale Fellowship for Biblical Research
Keywords: Bible. N.T. Peter, 2nd -- lectures